(untitled) (Journal of Plant Disease Sciences, 2019)
Among the bacteria colonizing plant rhizosphere, Pseudomonas spp. plays an important role both as a plant growth stimulating agent as well as a biocontrol agent. Eight fluorescent pseudomonads were identified based on their morphological characters, physiological and biochemical tests. All the isolates of fluorescent pseudomonads were gram negative had circular colonies and majority of them had creamy white colored colonies. Isolate FP-2, FP-3, FP-6 and FP-8 had smooth glossy colony surface, whereas, isolate FP-1 and FP-4 produced smooth surface and isolate FP-5 showed rough surface. All the isolates were positive for gelatin liquefaction, catalase and oxidase and negative reaction for starch hydrolysis. Isolates FP-1, FP-2, FP-4, FP-6 and FP-8 grew at 4º C temperature and other isolates did not grow at 4º C. Growth of isolates FP-3, FP-5 and FP-7 was normal at 42º C whereas, rest of the isolates did not grow at that temperature.